Price setting behaviour in Spain: stylised facts using consumer price micro data - Luis J. Álvarez; Ignacio Hernando (European Central Bank (ECB), 2004)
This paper identifies the basic features of the price setting mechanism in the Spanish economy, using a large dataset that contains over 1.1 million price records and covers around 70% of the expenditure on the CPI basket. In particular, the paper identifies differences in the frequency and size of price adjustments across types of products and explores how these general features are affected by certain specific factors: seasonality, the level of inflation, changes in indirect taxation and the practice of using psychological and round prices. We find that prices do not change often but do so by a large amount, although there is a marked heterogeneity across products. Moreover, the high frequency of price reductions suggests that there is no strong downward rigidity. Our evidence also supports the use of time and state-dependent pricing strategies.
Keywords: E31; D40; C25; 330; consumer prices; frequency of price changes; price setting